2,4-Disubstituted pyridine derivatives are effective against intracellular and biofilm-forming tubercle bacilli - Korycka-Machała, M.; Kawka, M.; Lach, J.; Płocińska, R.; Bekier, A.; Dziadek, B.; Brzostek, A.; Płociński, P.; Strapagiel, D.; Szczesio, M.; Gobis, K.; Dziadek, J. (Frontiers in Pharmacology, 2022)
It was recently reported that 4-substituted picolinohydrazonamides carrying hydrophilic cyclic amines, such as morpholine and pyrrolidine, at the end of their thiosemicarbazide chain have potent antimycobacterial activity in vitro at concentrations below 1 µg/mL. Here, two selected compounds, 2,4-disubstituted pyridine derivatives 11 and 15, revealed significant bactericidal activity against Mycobacterium tuberculosis localized intracellularly within human macrophages, as well as against biofilm-forming tubercle bacilli. Mutants were selected that were resistant to the investigated compounds at an efficiency similar to that identified in the presence of the first line antituberculosis drug rifampicin. The resistant mutants were viable in the presence of the tested compounds exclusively on solid media. Genome-wide sequencing of the mutants selected in the presence of compound 11 revealed the accumulation of nonsynonymous mutations in the mmpR5 gene encoding a transcriptional repressor of the MmpS5-MmpL5 efflux pump, whose upregulation has been associated with bedaquiline resistance. The depletion of MmpR5 in wild-type M. tuberculosis using CRISPR–Cas9 technology increased the resistance of this strain to compound 11. Mass spectrometry-based proteomics (LC–MS/MS) of wild-type tubercle bacilli growing in subinhibitory concentrations of compounds 11 or 15 revealed 15 overproduced proteins not detectable in the control cells, including virulence-related proteins.